Pars Plana Vitrectomy versus Intravitreal Injection of Ranibizumab in the Treatment of Diabetic Macular Edema Associated with Vitreomacular Interface Abnormalities. (13th January 2021) - Elkayal, Hassan; Bedda, Ahmed M.; El-Goweini, Hesham; Souka, Ahmed A.; Gomaa, Amir Ramadan
Abstract : Purpose . To compare the efficacy of pars plana vitrectomy (PPV) versus intravitreal injection (IVI) of ranibizumab (RBZ) in the treatment of diabetic macular edema (DME) associated with vitreomacular interface abnormalities (VMIA). Methods . The records of patients presenting with DME and VMIA throughout 2016 to 2018 were retrospectively analyzed. The patients were divided into 2 groups: group I received IVIs of RBZ and group II underwent PPV with internal limiting membrane peeling. The main outcome measures were the change in the LogMAR corrected distance visual acuity (CDVA) and central subfield thickness (CSFT) on optical coherence tomography over 6 months. Results . At 6 months, mean CDVA improved by 0.22 ± 0.21 in group I patients p < 0.001, while in group II, it improved only by 0.09 ± 0.22 p < 0.115 . Fifty-five percent of group I and 60% of group II patients had stable CDVA (within 2 lines from baseline) at 6 months. Significant improvement in vision (gain of 2 or more lines) was seen in 45% and 30%, respectively. Worsening of vision (loss of 2 or more lines) was seen only in 2 patients in group II, but none in group I. The mean CSFT improved significantly in both groups (by 162 µ and 216 µ, respectively; p < 0.001 ). The mean CSFT at 6 months was similar in both groups (354 µ and 311 µ, respectively; p = 0.172 ). Conclusions . Both treatments resulted in anatomical improvement of DME with concurrent VMIA. Visual improvement was more pronounced in the IVI group, although this may have been affected by other confounding factors.